2012
DOI: 10.1185/03007995.2012.721760
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine liposome injectable suspension compared with bupivacaine HCl for the reduction of opioid burden in the postsurgical setting

Abstract: In this pooled analysis from nine studies representing five different surgical procedures, liposome bupivacaine administered at doses ≤266 mg in a multimodal setting was associated with statistically significant and clinically meaningful lower cumulative pain score at 72 h, delayed and less consumption of opioids, and fewer ORAEs than bupivacaine HCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
93
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(98 citation statements)
references
References 24 publications
1
93
0
Order By: Relevance
“…After approximately 72 hours, when the liposomal bupivacaine effect has worn off, the narcotic consumption in the two groups of patients was not statistically different. Dasta et al [8] demonstrated findings favoring liposomal bupivacaine compared with patient-controlled analgesia in a combined gastrointestinal and orthopaedic surgery trial, in which they reported reductions in pain intensity scores, as measured by a pooled area under the curve analysis, and reductions in total opioid use over 72 hours postoperatively. The clinically related significance of the reduction in pain scores remains unclear; however, they found a reduction in opioid-related adverse events in patients receiving liposomal bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…After approximately 72 hours, when the liposomal bupivacaine effect has worn off, the narcotic consumption in the two groups of patients was not statistically different. Dasta et al [8] demonstrated findings favoring liposomal bupivacaine compared with patient-controlled analgesia in a combined gastrointestinal and orthopaedic surgery trial, in which they reported reductions in pain intensity scores, as measured by a pooled area under the curve analysis, and reductions in total opioid use over 72 hours postoperatively. The clinically related significance of the reduction in pain scores remains unclear; however, they found a reduction in opioid-related adverse events in patients receiving liposomal bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that liposomal bupivacaine can improve the duration of effectiveness for PAI and thus may provide sufficient analgesia while also reducing the amount of opioid medications delivered for effective pain control. The current study occurred in settings that already had established total joint pathways in place, including preoperative education [70], patient-focused care initiatives [3,17,19,36,43,45,60,67,87], multimodal analgesia regimens [9,10,16,20,24,26,35,38,53,72,76,78,80,83], and postoperative rehabilitation pathways [16,51,77] to focus the results on the three randomized treatment groups described. We found that the primary outcome measure of pain control was better at 6 and 12 hours postoperatively in the liposomal bupivacaine PAI and spinal morphine groups compared with the ropivacaine PAI group.…”
Section: Discussionmentioning
confidence: 99%
“…14 Liposome bupivacaine has been shown to provide postsurgical analgesia across a range of surgical models, with a safety profile that is similar to that of bupivacaine HCl. [15][16][17] While available data in volunteers suggest that liposome bupivacaine in a femoral nerve block results in prolonged blockade, 18 its analgesic effects when used in a peripheral nerve block in a setting of acute postsurgical pain remain unknown.…”
mentioning
confidence: 99%